1982
DOI: 10.1073/pnas.79.23.7420
|View full text |Cite
|
Sign up to set email alerts
|

Mucolipidosis III is genetically heterogeneous.

Abstract: Mucolipidosis m (ML HI), or pseudo-Hurler polydystrophy, is an inherited childhood disorder characterized biochemically by low activities and abnormal electrophoretic patterns of multiple lysosomal enzymes in fibroblasts. The primary deficiency of ML Im has been proposed to be in UDP-N-acetylglucosamine:lysosomal enzyme N-acetylglucosamine-l-phosphotransferase. However, variation in this enzyme and in other biochemical properties of different ML mI lines has been observed. Therefore, we investigated genetic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…The genetic relationships between the multiple variants of MLII and MLIII are complex and have been difficult to understand in the absence of information about the gene(s) involved (14)(15)(16)35). This study demonstrates the MLIII(C) phenotype can result from a mutation in the GlcNAc-phosphotransferase γ subunit.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The genetic relationships between the multiple variants of MLII and MLIII are complex and have been difficult to understand in the absence of information about the gene(s) involved (14)(15)(16)35). This study demonstrates the MLIII(C) phenotype can result from a mutation in the GlcNAc-phosphotransferase γ subunit.…”
Section: Discussionmentioning
confidence: 94%
“…Heterokaryon analysis has been used to divide MLIII into 3 distinct complementation groups (15,16). Complementation group A (classic MLIII) is characterized by moderately decreased GlcNAc-phosphotransferase activity measured on all substrates.…”
mentioning
confidence: 99%
“…6 A series of genetic-complementation studies have shown heterogeneity in ML III and the genetic relationship between ML II and III. [7][8][9] Mutations in GNPTAB cause both the severe type of ML (ML II alpha/beta, ML II, I-cell disease (MIM 252500)) and the attenuated type of ML (ML III alpha/beta, ML IIIA, PseudoHurler polydystrophy (MIM 252600)). [10][11][12] Mutations in GNPTG cause the attenuated type of ML (ML III gamma, ML IIIC, ML III variant (MIM 252605)).…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts from patients with ML-II have extremely low or undetectable enzyme levels, whereas fibroblasts from patients with ML-III have some residual phosphorylating activity consistent with their milder clinical course (38)(39)(40)(41)(42). Cell fusion experiments have defined complementation groups among various ML-II and ML-III fibroblast lines (69,70). The ML III lines have been placed into two distinct complementation groups, with the possible existence of a third (69).…”
mentioning
confidence: 99%